Welded joint of martensitic stainless steel, welding structure and welding method
By adjusting chemical composition and controlling welding thermal history, the problem of insufficient heat-affected zones of martensitic stainless steel is solved without preheating or high-temperature heat treatment, and the good performance and reliability of the welding structure are achieved.
Patent Information
- Application Number
- JP2023145358
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-19
AI Technical Summary
Martensitic stainless steel has poor weldability, especially when preheating or high-temperature heat treatment is not performed, it is prone to low-temperature cracks and insufficient heat-affected zones (HAZs) toughness, making it difficult to apply to welding structures in practical applications.
By adjusting chemical composition and controlling welding heat history, ensuring that grain size distribution in the welding heat-affected zone is 80% or higher with an area ratio of 0.04 mm or smaller, specific welding methods and conditions are used, such as controlling the time for temperatures exceeding 1250°C for 8 seconds or less to inhibit grain coarsening.
It effectively improves the toughness of the heat-affected zone (HAZ) after welding, avoids the occurrence of low-temperature cracks, and ensures the overall performance and reliability of the welded structure.
Smart Images

Figure 2025038629000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a welded joint of martensitic stainless steel, a welded structure having the joint, and a welding method for martensitic stainless steel. [Background technology]
[0002] Martensitic stainless steel is a Cr-based stainless steel that has a hard martensite phase that is formed by quenching from a high-temperature austenite phase state. Its hardness is used for blades, shafts, etc. SUS410 is known as a martensitic stainless steel, and since it contains less expensive elements such as Ni and Mo and has a relatively lower Cr content than other stainless steels, it is also a relatively inexpensive stainless steel with a reasonable level of corrosion resistance (for example, Patent Document 1 and Patent Document 2).
[0003] The application of this martensitic stainless steel to storage facilities such as the holds of general-purpose transport tankers and general-purpose storage tanks is being considered. In the case of general-purpose storage facilities, the stored goods are frequently changed, and the inside of the storage facilities must be cleaned every time the stored goods are changed. Currently, even for general-purpose use, a certain degree of corrosion resistance is required, so regular painted steel plates are used. However, with painted steel plates, the paint is damaged by cleaning, and repairing it takes a lot of time and effort. For this reason, efforts are being made to eliminate damage caused by cleaning, and to improve the efficiency and cost of cleaning processes by using stainless steel that can be used without painting instead of painted steel plates for storage facilities. The application of martensitic stainless steel, which is relatively inexpensive and has a certain degree of corrosion resistance, is being considered as such stainless steel. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 49-53521 [Patent Document 2] JP 2011-190521 A [Patent Document 3] International Publication No. 2016 / 088364 Summary of the Invention [Problem to be solved by the invention]
[0005] In general, martensitic stainless steels have poor weldability and are not used in welded structures. The reason is that they have a high so-called low-temperature cracking sensitivity, which requires preheating at 200 to 400°C, which is a bottleneck in practical applications. Furthermore, the toughness of the welded heat affected zone (HAZ) is poor, so high-temperature heat treatment at about 700 to 800°C is required to improve the toughness. For this reason, as a practical problem, a heat treatment furnace capable of preheating and high-temperature heat treatment of the welded structure is required, and therefore martensitic stainless steels are not used in welded structures.
[0006] Patent Document 1 proposes a martensitic stainless steel that can be welded without preheating and has ductility and toughness even in the welded state. This is achieved by reducing C and N and adjusting the composition to generate a massive martensite structure with good ductility and toughness in the HAZ. However, although the cracking sensitivity has been improved, the HAZ toughness after welding is not necessarily sufficient when welding thick materials with a large heat input that provides good workability.
[0007] Patent Document 2 proposes a martensitic stainless steel that achieves both weld toughness and corrosion resistance while suppressing the content of expensive Ni. This is a 16%Cr-2%Ni steel based on which 2% or more of Mn is added to improve the toughness of the weld. This allows the weld toughness to be secured without heat treatment after welding while maintaining a certain degree of corrosion resistance. However, Mn is an element that reduces corrosion resistance. Mn is added to ensure the toughness of the weld, but the Cr content is increased to compensate for the reduced corrosion resistance, and the Ni content is also increased to ensure the amount of austenite. This makes it expensive, and in terms of cost performance, it is no different from ferritic or duplex stainless steels.
[0008] Patent Document 3 describes that in circumferential welding of low-carbon martensitic stainless steel pipes, the low-temperature toughness of the weld metal can be improved by performing the first pass by CMT (Cold Metal Transfer) welding, and that there is no practical problem even if post-weld heat treatment is not performed. However, it is the fracture toughness of the weld metal that is improved in toughness, not the HAZ toughness of the base metal. In order to improve the HAZ toughness of the base metal, post-weld heat treatment is required.
[0009] On the other hand, when applying martensitic stainless steel to storage facilities, it is practically impossible to perform preheating or post-weld heat treatment when welding because the storage facilities themselves are large. In particular, when martensitic stainless steel with a plate thickness of 10 mm or more used for storage facilities is welded, the toughness of the HAZ decreases significantly, leading to a decrease in the functionality of the structure.
[0010] Therefore, the present invention aims to improve the toughness of the HAZ in a welded joint of martensitic stainless steel without causing low-temperature cracking even without preheating or high-temperature heat treatment, and to provide a welded joint of martensitic stainless steel with improved HAZ toughness, a welded structure having such a welded joint, and a welding method. [Means for solving the problem]
[0011] In order to achieve the above object, the present inventors have conducted extensive research and have obtained the following findings. (a) The mechanism of the toughness deterioration and improvement of HAZ during welding of martensitic stainless steels was investigated. The temperature change over time due to welding was calculated by simulation for various martensitic stainless steels, and the resulting change in HAZ structure was confirmed by experiments. As a result, it was found that the martensite phase in the HAZ becomes coarse due to the heat input during welding, which is the cause of the deterioration of toughness.
[0012] (b) Next, the relationship between grain size distribution and HAZ toughness was evaluated. In the case of martensite phase, it is difficult to distinguish grain boundaries in normal microstructural observation, making it difficult to quantitatively calculate grain size distribution. Therefore, the grain size distribution of the ferrite phase in the HAZ was measured using EBSD (electron backscatter diffraction) and the relationship with HAZ toughness was evaluated. The reason for evaluating the ferrite phase here is that martensite phase is also recognized as a ferrite phase in EBSD. In addition, the grain size distribution can be obtained using software that comes with EBSD. As a result, it was found that good toughness, specifically, absorbed energy of 27 J or more at -20°C can be secured if the area ratio of crystals with a grain size (area equivalent circle diameter) of 0.04 mm or less is 80% or more.
[0013] (c) Furthermore, they investigated the coarsening of crystal grains, and found that when martensitic stainless steel is heated to a high temperature close to the melting point near the weld fusion line, part of the weld heat-affected zone in the base material transforms into a single phase of ferrite (single ferrite phase) via the austenite phase, and because the self-diffusion rate of elements in this ferrite phase is faster than that of the austenite phase, the crystal grains coarsen rapidly at temperatures above the temperature at which the ferrite phase becomes single phase (single ferrite phase temperature), and when cooled, these coarse grains continue to become coarse martensite phase.
[0014] (d) We also investigated the welding thermal history that results in coarse grains that result in poor HAZ toughness. In a composition system with low C and N and minimal amounts of expensive elements such as Ni and Mo to reduce cold cracking susceptibility, the ferrite single phase temperature is approximately 1250°C. We found that if the time at a temperature above this ferrite single phase temperature is within 8 seconds, coarsening of grains can be suppressed and the grain size can be kept within the acceptable range.
[0015] The present invention has been made by integrating these findings, and the gist of the present invention is as follows.
[0016] [1] At least one of them is, in mass%, C: 0.030% or less Si: 1.00% or less Mn: 0.10-3.00%, P: 0.050% or less, S: 0.003% or less, Cr: 10.0-12.5%, Ni: 0.50-2.00%, N: 0.0200% or less, Cu: 2.00% or less, Al: 0.050% or less Including, C+N: 0.040% or less; The balance is Fe and unavoidable impurities, A welded joint that is a martensitic stainless steel having a γmax of 75 or more as shown in Formula 1, A martensitic stainless steel welded joint, characterized in that when a histogram of crystal grain size is measured using EBSD (electron backscatter diffraction) in a coarse-grained region in the weld heat affected zone of a cross section of the welded joint, the area ratio of crystals with a grain size of 0.04 mm or less is 80% or more. γmax=420C+470N+23Ni+9Cu+7Mn-11.5Cr-11.5Si-52×Al+189: Formula 1 In the formula 1, the element symbols indicate the content (mass%) of each element, and 0 is substituted if the element is not contained. [2] The martensitic stainless steel further comprises, in mass %, Mo: 1.00% or less W: 0.50% or less, V: 0.300% or less, Sn: 0.100% or less, Ca: 0.0050% or less, Mg: 0.0050% or less, REM: 0.050% or less, Ti: 0.020% or less, Nb: 0.050% or less, B: 0.0050% or less, A welded joint of martensitic stainless steel according to [1], which contains one or more of the following: [3] The martensitic stainless steel welded joint according to [1] or [2], which is a welded joint between martensitic stainless steels. [4] A method for manufacturing a welded joint of a martensitic stainless steel having the composition described in [1] or [2] above, A method for manufacturing a welded joint of martensitic stainless steel, characterized in that in the weld heat-affected zone, the time during which the temperature remains at or above 1250°C is 8 seconds or less from the time when the temperature last reached 1250°C or higher due to heating by welding. [5] A welded structure, at least in a part thereof, comprising a welded joint made of the martensitic stainless steel according to any one of [1] to [3] above. Effect of the Invention
[0017] The method for welding martensitic stainless steel according to the present invention has the effect of suppressing the decrease in HAZ toughness, and the welded joint of martensitic stainless steel according to the present invention provides a welded joint with good HAZ toughness. Furthermore, the welded joint according to the present invention makes it possible to obtain a welded structure with good toughness. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is an example of a microstructure photograph of a cross section of a welded joint of a martensitic stainless steel material according to the present invention. [Diagram 2] Figure 2 shows an example of the results of measuring the part including the coarse grain region in Figure 1 using the EBSD method. [Diagram 3] FIG. 3 shows the results of cutting out the coarse-grained region from FIG. [Figure 4] FIG. 4 is a diagram showing an example of the cumulative area ratio at grain size intervals of 5 μm, based on the grain size measurement results of FIG. 3 and the results of similar evaluation of three other steel types. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] [Components of martensitic stainless steel] An example of an embodiment of the present invention will be described below. Unless otherwise specified, "%" regarding the content of an element means mass%. Furthermore, when no lower limit is specified, it may include the case where no element is contained (0%). Furthermore, when an element symbol is used in a formula, the element symbol indicates the content (mass%) of each element, and when no element is contained, 0 (%) is substituted.
[0020] C: 0.030% or less C has the effect of improving strength, but at the same time increases susceptibility to weld cracking. For this reason, in the steel according to the present invention, which does not require preheating during welding, it is preferable to reduce the C content as much as possible, to 0.030% or less. The upper limit of the C content can preferably be 0.028%, 0.026%, 0.024%, 0.022%, 0.020%, or 0.018%. On the other hand, the lower limit of the C content is not particularly limited and may not be included (0%). However, since an excessive reduction in the C content leads to an extreme increase in costs, the lower limit may be set to 0.001%, and preferably to 0.002%, 0.003%, 0.004%, or 0.005%.
[0021] Si: 1.00% or less Silicon has a deoxidizing effect during refining and is also useful for suppressing the formation of oxide scale during heat treatment, but since silicon widens the temperature range of the ferrite single phase and reduces toughness, the content is set to 1.00% or less. From the viewpoint of narrowing the temperature range of the ferrite single phase, the upper limit of the silicon content can be 0.90%, 0.80%, 0.70%, 0.60%, 0.55%, 0.50%, 0.45%, or 0.40%. On the other hand, the lower limit of the Si content is not particularly limited and may be absent (0%). However, since Si is also a deoxidizing element in the refining process, the lower limit of the Si content may be 0.01%, and preferably may be 0.03%, 0.05%, 0.08%, 0.10%, 0.13%, 0.15%, 0.17%, or 0.18%.
[0022] Mn: 0.10-3.00% Mn has a deoxidizing effect during refining and narrows the ferrite single phase region. To obtain this effect, the Mn content should be 0.10% or more. To ensure that the ferrite single phase region is narrowed, the lower limit of the Mn content can be 0.20%, 0.30%, 0.40%, 0.50%, or 0.60%. On the other hand, since excessive Mn reduces corrosion resistance and promotes the formation of oxide scale, the Mn content should be 3.00% or less. Taking into account the reduction in corrosion resistance caused by MnS and other granular substances, the upper limit of the Mn content can be 2.80%, 2.60%, 2.50%, 2.30%, 2.10%, 2.00%, 1.80%, 1.60%, or 1.50%.
[0023] P:0.050% or less P is an element contained as an impurity in the main raw materials such as molten iron and ferrochrome. Since P is an element that is the main cause of the decrease in hot ductility, it is better to reduce its content as much as possible. From this viewpoint, the P content should be 0.050% or less. Preferably, the upper limit of the P content should be 0.045%, 0.040%, 0.035%, or 0.030%. However, an excessive reduction leads to an extreme increase in costs, so the lower limit of the P content is preferably 0.001%, 0.005%, or 0.010%.
[0024] S: 0.0030% or less S is an element that forms sulfide-based inclusions and deteriorates the general corrosion resistance (general corrosion and pitting corrosion) of steel materials, and also reduces hot ductility and increases the edge cracking sensitivity of hot-rolled steel sheets, so its content is preferably as low as possible. In addition, when S and P coexist, it may particularly reduce hot ductility and increase cracking sensitivity, so S is particularly limited and the S content is set to 0.0030% or less. From these points of view, it is better to have as low an S content as possible, so its upper limit is preferably 0.0020% or 0.0010%. On the other hand, the lower the S content, the better the hot workability and corrosion resistance, but reducing S increases the desulfurization load and increases the manufacturing cost, so the lower limit of the content may be 0.0001%, and preferably 0.0003%.
[0025] Cr: 10.00~12.50% In order to ensure corrosion resistance in martensitic stainless steel, the Cr content is preferably 10.00% or more. From the viewpoint of ensuring corrosion resistance, the lower limit of the Cr content can preferably be 10.20%, 10.30%, 10.50%, 10.70%, 10.90%, 11.00%, 11.20%, or 11.30%. On the other hand, if the Cr content is too high, the ferrite single phase temperature range is expanded to the low temperature side and grain coarsening becomes severe, so the Cr content is set to 12.50% or less. The upper limit of the Cr content can preferably be 12.40, 12.30, 12.20, 12.10, 12.00, 11.90, 11.80, 11.70, 11.60, or 11.50%.
[0026] Ni: 0.50~2.00% Ni, like Mn, is an austenite stabilizing element and has the effect of reducing the ferrite single phase region, improving toughness, and further suppressing the development of pitting corrosion. From this viewpoint, the Ni content is set to 0.50% or more. From the viewpoint of ensuring these effects, the lower limit of the Ni content can be 0.55%, 0.60%, 0.65%, or 0.70%. On the other hand, if a large amount of Ni is contained, a residual austenite phase is generated, which reduces hardness, and from the viewpoint of alloy cost, the Ni content is set to 2.00% or less. The upper limit of the Ni content can be 1.80%, 1.60%, 1.40%, 1.20%, 1.00%, 0.90%, or 0.80%.
[0027] N: 0.0200% or less N is an austenite forming element, but like C, it increases weld crack susceptibility, so it is best to reduce it as much as possible, and the N content is set to 0.0200% or less. The upper limit of the N content can preferably be 0.0180%, 0.0160%, 0.0150%, 0.0140%, 0.0130%, 0.0120%, 0.0110%, or 0.0100%. On the other hand, the lower limit of the N content is not particularly limited and may not be included (0%). However, since an excessive reduction in the N content leads to an extreme increase in costs, the lower limit may be set at 0.0010%, and preferably, the value may be 0.0030% or 0.0050%.
[0028] Cu:2.00% or less Cu may be added since it has an austenite stabilizing effect. However, excessive Cu content leads to a decrease in hot workability and an increase in raw material costs, so the Cu content is set to 2.00% or less. The upper limit of the Cu content can preferably be 1.80%, 1.60%, 1.40%, 1.20%, 1.00%, 0.90%, 0.80%, 0.70%, 0.60%, or 0.50%. Since Cu may not be contained, the lower limit of the Cu content is 0%, but since removing Cu is costly, the lower limit of the Cu content may be 0.01%, and preferably 0.10% or 0.20%.
[0029] Al: 0.050% or less Al is a deoxidizing element and improves oxidation resistance, so it may be contained. On the other hand, excessive Al content tends to form large oxide-based inclusions, impairing toughness. For this reason, the Al content is set to 0.050% or less. It can preferably be 0.040% or 0.030%. Since Al is not necessary, the lower limit of the content is 0%, but since removing Al is costly, the lower limit of the Al content may be 0.001%. Preferably, the value can be 0.005%, 0.008%, 0.010%, or 0.015%. Here, the Al content is the T.Al (total Al) content.
[0030] C+N: 0.040% or less Carbon (C) has the effect of increasing the strength of steel when combined with nitrogen (N), but it also increases susceptibility to weld cracking. In order to prevent weld cracking even without preheating, the total amount of C and N (C+N) is limited to 0.040% or less. The upper limit of the total amount of C and N (C+N) can preferably be 0.039%, 0.038%, 0.037%, 0.036%, 0.035%, 0.034%, 0.033%, 0.032%, 0.031%, 0.030%, 0.029%, 0.028%, 0.027%, 0.026%, or 0.025%.
[0031] In one embodiment of the present invention, the balance is Fe and inevitable impurities in addition to the above elements. Here, the inevitable impurities refer to elements that are inevitably and unintentionally mixed in raw materials such as ores and scraps during the industrial production of steel, and are permissible within a range that does not adversely affect the present invention.
[0032] Furthermore, in addition to these elements, the stainless steel of this embodiment may contain one or more of Mo, V, Sn, Ca, and REM in place of a portion of Fe. These elements do not have to be contained, but by containing them, further effects can be obtained. These elements will be described below.
[0033] Mo: 1.00% or less Mo may be added because it is effective in improving the corrosion resistance of martensite structures containing δ-ferrite. However, Mo is a stabilizing element for the ferrite phase, and excessive addition of Mo increases the amount of ferrite phase in the HAZ, as with Cr. Furthermore, Mo is an expensive element, so the Mo content is set to 1.00% or less. The upper limit of the Mo content can preferably be 0.90%, 0.80%, 0.70%, 0.60%, 0.50%, 0.45%, 0.40%, 0.35%, 0.30%, 0.25%, 0.20%, 0.15%, or 0.10%. The lower limit of the Mo content is not particularly limited, but since removing Mo is costly, it is preferable that the lower limit be 0.005% or 0.01%.
[0034] W: 0.50% or less W, like Mo, is an element that improves the corrosion resistance of stainless steel and may be contained. However, since it is an expensive element, it is preferable to keep the content at 0.50% or less, and preferably at 0.40% or less or 0.30% or less. When W is contained, it is preferable to contain 0.01% or more in order to obtain the effect more reliably, preferably 0.05% or more, and more preferably 0.10% or more.
[0035] V:0.300% or less V may be contained since it forms fine carbonitrides and is effective in improving the wear resistance as well as the corrosion resistance. However, excessive V content may cause the precipitates to become coarse, resulting in a decrease in toughness, so the upper limit of the V content is 0.300%, preferably 0.200% or 0.100%. The lower limit of the V content is not particularly limited, but considering the production cost and manufacturability, it is preferably 0.010%, 0.030%, 0.050%, or 0.070%.
[0036] Sn: 0.100% or less Sn is an effective element for improving corrosion resistance after quenching, but excessive addition promotes edge cracking during hot rolling. Therefore, the upper limit of the Sn content is 0.100%, preferably 0.090%, 0.080%, 0.070%, 0.060%, or 0.050%. There is no particular limit to the lower limit of the Sn content, but from the viewpoint of ensuring the effect, it is preferably 0.001%, preferably 0.002%, 0.005%, 0.010%, 0.015%, or 0.020%.
[0037] Ca: 0.0050% or less Mg: 0.0050% or less Ca and Mg may be added to adjust the composition at the steelmaking stage, and may be included since they act as strong deoxidizers, promoting deoxidation and improving hot ductility. However, there is a concern that they may reduce corrosion resistance, so the Ca and Mg contents are set to 0.0050% or less. The upper limits of the Ca and Mg contents can preferably be 0.0030% and 0.0020%, respectively. There is no particular lower limit for the Ca or Mg content, but from the standpoint of ensuring the desired effect, the lower limit should be 0.0001%, preferably 0.0002%, 0.0003%, 0.0004%, or 0.0005%, respectively.
[0038] REM: 0.050% or less The inclusion of an appropriate amount of REM can significantly improve hot ductility, similar to the inclusion of Ca. To obtain this effect, the lower limit of the REM content should be set to 0.001%, 0.002%, 0.003%, 0.004%, or 0.005%. On the other hand, excessive addition of REM is undesirable because it tends to form large REM oxides, which can cause nozzle clogging during casting. The upper limit of the REM content should be set at 0.050% or 0.030%. REM is usually added in the form of a complex misch metal, but the addition of single elements such as La, Ce, Pr, and Nd also has the same effect. Here, REM (rare earth elements) refers to the two elements scandium (Sc) and yttrium (Y) and the 15 elements (lanthanoids) from lanthanum (La) to lutetium (Lu), as generally defined. These REM elements may be contained alone or in combination. If multiple REM elements are contained, the total amount should be within the above lower and upper limits.
[0039] Ti: 0.020% or less Nb: 0.050% or less B: 0.0050% or less Ti and Nb have the effect of improving corrosion resistance, and B has the effect of improving hot ductility, so Ti: 0.020% or less, Nb: 0.050% or less, and B: 0.0050% or less may be contained. Although it is not necessary to contain each of the elements Ti, Nb, and B, it is also not necessary to remove them excessively. Therefore, the lower limit of the content of each of these elements is not particularly limited, but it may be Ti: 0.001%, Nb: 0.010%, and B: 0.0001%.
[0040] It is also preferable to reduce the amount of Zn, Pb, Bi, Se, Sb, Ga, Ta, Mg, Zr, etc. as much as possible. On the other hand, these elements may contain one or more of the following amounts as necessary to solve the problems of the present invention: Zn: 50 ppm or less, Pb: 10 ppm or less, Bi: 30 ppm or less, Se: 100 ppm or less, Sb: 100 ppm or less, Ga: 50 ppm or less, Ta: 500 ppm or less, Mg: 100 ppm or less, and Zr: 120 ppm or less.
[0041] [γmax≧75] γmax is shown by formula 1, and is an index for predicting the maximum value of the austenite phase fraction generated in the range of 900°C to 1000°C. Here, the element symbols in formula 1 indicate the content (mass%) of each element, and 0 is substituted when the element is not contained. γmax=420C+470N+23Ni+9Cu+7Mn-11.5Cr -11.5Si-52×Al+189 ...Formula 1
[0042] The larger γmax is, the higher the austenite phase ratio is near 1000°C. Also, the larger γmax is, the wider the temperature range in which the austenite phase is formed with respect to temperature changes near 1000°C. In addition, the ferrite single phase temperature range at high temperatures is narrowed, and the coarsening of the ferrite phase during welding can be suppressed. The inventors' experiments confirmed that if γmax is 75 or more, the ferrite single phase temperature can be approximately 1250°C. Since the larger γmax is, the more preferable it is, the lower limit value can preferably be 80, 85, or 90. There is no particular limit to the upper limit. The upper limit is automatically determined according to formula 1 from the component range of martensitic stainless steel.
[0043] [Manufacturing method of martensitic stainless steel] The manufacturing method of the martensitic stainless steel described above is not particularly limited. It can be manufactured by applying a conventional manufacturing method. Since it is a low C+N steel (steel containing low carbon and low nitrogen), it is not extremely hard and has relatively good toughness, so unlike general martensitic stainless steel, it does not require long-term annealing, and it can have sufficient properties by performing a short-term tempering heat treatment at about 700°C to 800°C after water cooling or air cooling to form a martensite phase after hot rolling.
[0044] Plate Thickness There are no particular limitations on the thickness of the martensitic stainless steel plate that constitutes the welded joint, but if it is thin, there is no need to increase the welding heat input, and thus coarse grains are less likely to form in the first place, and the toughness itself is better with a thinner plate thickness, so there is less need to use the welding method of the present invention, so a plate thickness of 6 mm or more, 8 mm or more, 10 mm or more, 12 mm or more, 15 mm or more, 20 mm or more, 25 mm or more, or 30 mm or more is preferable.
[0045] [Weld heat affected zone structure] Next, we will explain the requirements for ensuring HAZ toughness. Figure 1 shows an example of a microstructural observation of a welded joint cross section. This was taken by embedding a cross section perpendicular to the weld line of a welded joint in resin, polishing it to a mirror finish, etching it with aqua regia, etc., and observing it under a microscope and taking a photograph. Within this, the area in the HAZ where coarse grains have occurred can be clearly identified as "5 (coarse grain area)" in Figure 1.
[0046] Although the size of this coarse-grained region 5 varies depending on the amount of welding heat input, in normal welding, it is a region within about 1 mm on the base metal side of the fusion boundary line 3. The fusion boundary line 3 is the boundary between the weld metal 2 that constitutes the welded joint and the martensitic stainless steel 1 that serves as the base metal. The range of 1 mm from the fusion boundary line 3 refers to a region within the stainless steel 1 that serves as the base metal, within a range of 1 mm from the fusion boundary line 3 in a cross section perpendicular to the weld line of the welded joint.
[0047] The coarse-grained region was measured by EBSD (electron backscatter diffraction), and the results are shown in Figure 2, where each crystal grain of the ferrite phase is colored in a different color. In this analysis, the analysis range is rectangular, and includes the base material part that is not coarse-grained region 5 and weld metal 2. Weld metal 2 can be excluded because it will become an austenitic phase if the welding rod is austenitic, but the base material part that is not coarse-grained region 5 must be explicitly cut out. Figure 3 shows only the coarse-grained region 5. From the grain size summary results of the coarse-grained region 5 obtained in this way by EBSD, a histogram was created in 5 μm grain size increments, and the area ratio of each was accumulated from the larger grain size side. Figure 4 shows the results. These can be output using a program attached to EBSD. In Figure 4, unlike No. 74, which has low HAZ toughness, No. 56 and 54, which have good HAZ toughness, have a small area ratio of coarse grains. As a result of various evaluations, it was found that if the area ratio of crystal grains with a grain size (area equivalent circle diameter) of 0.04 mm or less is 80% or more, good HAZ toughness, specifically, a Charpy absorbed energy of 27 J or more at -20°C can be ensured. To obtain better HAZ toughness, the area ratio of crystals with a grain size of 0.04 mm or less is preferably 85%, 90%, or 95%.
[0048] [Welding conditions] Next, the welding conditions for obtaining the target grain size will be described. As mentioned above, in the case of steel with the composition of the present invention, the ferrite single phase temperature at which grain coarsening can occur is approximately 1250°C or higher. Below this temperature, two phases, ferrite phase and austenite phase, coexist, so grain coarsening hardly occurs. As a result of evaluating the relationship between the time elapsed at 1250°C or higher and the structure by a heating test simulating welding, it was found that the area ratio of crystals with a grain size of 0.04 mm or less can be made 80% or more by setting the elapsed time at 1250°C or higher from the time when the temperature finally reached 1250°C or higher by heating due to welding to 8 seconds or less in the weld heat affected zone. The time is preferably 7 seconds, 6 seconds, or 5 seconds or less.
[0049] The time elapsed above 1250°C is the time elapsed since the last time the temperature reached 1250°C or higher due to heating by welding, i.e., the time elapsed since the last welding pass exceeding 1250°C, and it is not necessary to take into account the passes prior to that. This is because even if the structure transforms into martensite once by lowering the temperature, when it is heated again, it undergoes a phase transformation twice, first to the austenite phase and then to the ferrite phase, resulting in a change to a fine structure.
[0050] In order to control the time that the weld heat-affected zone remains above 1250°C, a temperature history simulation calculation can be performed before welding to estimate the temperature history, and welding conditions can be found that will keep the time at 1250°C or higher to 8 seconds or less. Then, welding can be performed in accordance with these conditions.
[0051] [Welded joint] The structure of the welded joint in the embodiment of the present invention is not particularly limited. For example, a commonly used welded joint structure such as butt welding, fillet welding, or lap fillet welding can be adopted. The welding means is also not particularly limited as long as it satisfies the above-mentioned welding conditions. For example, existing welding means such as so-called arc welding such as TIG welding, MIG welding, MAG welding, plasma welding, and submerged welding, and laser welding can be applied. In particular, in the case of thick steel materials (thick plates) such as storage facilities, arc welding with a filler metal is common. In that case, the filler metal (welding wire, etc.) is not particularly limited, but it is preferable to use a filler metal for austenitic stainless steel or duplex stainless steel, which is compatible with martensitic stainless steel.
[0052] The steel materials constituting the welded joint may be a combination of steel materials including at least the martensitic stainless steel having the above-mentioned composition. In this case, the present invention is applied to improve the HAZ toughness of the martensitic stainless steel constituting the welded joint. Of course, the welded joint may be a welded joint between martensitic stainless steels having the above-mentioned composition. The present invention can be applied to improve the HAZ toughness of all welded joints between martensitic stainless steels.
[0053] The shape of the steel material is not particularly limited. It may be a strip-shaped steel material (steel plate), a bar-shaped steel material (steel bar), a linear steel material (wire material, wire, etc.), or a tubular steel material (steel pipe). Of course, it may be a combination of these steel materials.
[0054] [Welded structure] A structure constructed by welding, i.e., a structure having a welded joint, is called a welded structure. The welded structure according to the present invention is a welded structure having at least one or more welded joints as described above. By having the welded joint according to the present invention, the toughness of the welded joint can be ensured. EXAMPLES
[0055] Examples of the present invention will be described below. Note that the present invention is not limited to the conditions used in the following examples. Steel with the composition shown in Table 1 was melted in a MgO crucible in a 50 kg vacuum induction furnace in the laboratory and cast into a flat steel ingot with a thickness of approximately 100 mm. The main body of the steel ingot was processed into a hot rolling material, which was heated to a temperature of 1150 to 1250°C for 1 to 2 hours and then hot rolled into a hot-rolled steel plate with a thickness of 10 to 35 mm. The final solution heat treatment was performed under the conditions of 750°C x (plate thickness x 1 minute) soaking followed by water cooling. From the obtained hot-rolled plate, multiple strip-shaped steel test pieces (at least 4 pieces) with a length of 200 mm and a width of 100 mm were prepared.
[0056] First, the following tests were performed to determine whether the base material characteristics were acceptable. For hot workability, those that did not have edge cracks at the width end during hot rolling were deemed to have passed. For toughness, Charpy test pieces were taken from the base material and Charpy impact tests (-20°C absorbed energy) were performed in accordance with JIS Z 2242:2018, and those that had an average value of 80J or more were deemed to have passed. For corrosion resistance, samples were taken from the steel surface and polished with #600, and pitting potential measurements were performed in accordance with JIS G 0577. Those that had an average value of 0VvsAg / AgCl or more were deemed to have passed. In Table 1, those that passed each evaluation are indicated with "○" and those that failed are indicated with "×".
[0057] Next, for the evaluation of low-temperature cracking, two randomly selected pieces of each prepared steel test material were butted together under the same conditions and evaluated in accordance with the y-type restraint cracking test (JIS Z3158:2016) under the welding conditions in Table 2. The results are shown in Table 2. Test materials in which no cracks were observed are indicated with a "◯", and test materials in which cracks were observed are indicated with an "X".
[0058] Furthermore, for each prepared steel test material, two randomly selected pieces were butt-welded under the same conditions to create welded joints. A V-groove with a groove angle of 60° was made at the butt end of each test material, and the welding method and filler metal (welding material) shown in Table 2 were used. Welding was also performed with the welding current, welding voltage, and welding speed shown in Table 2. At this time, a thermal history simulation calculation was performed in advance to determine the maximum elapsed time of the last pass at which the HAZ reached 1250°C or higher. The number of passes ranged from 2 to 21, depending on the plate thickness and welding heat input.
[0059] In addition, for the welding methods shown in Table 2, "GMAW" stands for gas metal arc welding, "TIG" stands for tungsten inert gas welding, and "SAW" stands for submerged arc welding. In addition, for the filler metals (welding metals), "308", "309", and "2209" correspond to TS308, TS309, and TS2209 as well as TIG and SAW wires of the same steel type as specified in JIS Z 3323:2007 (Stainless steel arc welding flux-cored wires and filler rods).
[0060] The thus obtained welded joint test pieces (length 200 mm, width 200 mm) were subjected to cross-sectional observation and toughness evaluation.
[0061] After welding, the welded joint test material was cut perpendicular to the initial weld line at an arbitrary position in the longitudinal direction to obtain a test material for evaluation having a length of 20 mm. For one of the evaluation test pieces, the coarse grained region of the HAZ was identified by cross-sectional observation using an optical microscope, and a 10 x 10 mm test piece was taken from that area for EBSD measurement. The measurement results were analyzed using the accompanying software, and the coarse grained region was extracted from the results of painting each crystal grain of the ferrite phase with a different color (see Figure 2) (see Figure 3), and the area ratio of each crystal grain with a grain size of 0.04 mm or less in this range (coarse grained region) was calculated.
[0062] Furthermore, a Charpy test piece was taken from another evaluation test material with the notch position aligned with the coarsened grain area, and a Charpy impact test (-20°C absorbed energy) was performed in accordance with JIS Z 2242:2018. The absorbed energy of the three evaluation test pieces was arithmetically averaged to obtain the absorbed energy value of the welded joint, and an absorbed energy of 27 J or more in the Charpy impact test was considered to have passed. The test results are shown in Table 2.
[0063] As can be seen from Table 2, none of the welded joints of the examples of the present invention had low-temperature cracks, and the toughness of the welded heat-affected zone of the base metal was good. On the other hand, welded joints No. 62, 68, and 69, which were high C, N, or high C+N, respectively, had low-temperature weld cracks. Welded joints No. 67 and 72, which were high Cr and low γmax, respectively, did not meet the required value for the area ratio of the grain size of 0.04 mm or less in the coarse grain region, and had low toughness. Welded joints No. 63, 65, and 69, which were high Si, low Ni, and high Al, respectively, met the required value for the area ratio of the grain size of 0.04 mm or less in the coarse grain region, but had low HAZ toughness. Welded joints No. 64 and 66, which were high Mn and low Cr, respectively, lacked corrosion resistance of the base metal itself, and welded joint No. 69, which was high Cu, had good joint properties, but had poor hot ductility and cracks occurred during hot working of the base metal. Furthermore, since welded joints Nos. 73 to 76 were welded under conditions where the time at or above 1250°C exceeded 8 seconds, the area ratio of the coarse-grained regions with crystal grain sizes of 0.04 mm or less did not satisfy the required value, resulting in low toughness.
[0064] [Table 1]
[0065] [Table 2] [Industrial Applicability]
[0066] The present invention can be used in welded structures that use martensitic stainless steel plates, and its applications are not limited to storage facilities, but can be used in a wide range of industries, including general buildings, social infrastructure structures such as bridges, and mechanical equipment. [Explanation of symbols]
[0067] 1. Martensitic stainless steel material (base material) 2 Weld metal (austenite phase due to use of 309 series welding rod) 3. Melting Boundary 4. Welding heat affected zone 5 Coarse grain region
Claims
1. At least one of them is, in mass %, C: 0.030% or less Si: 1.00% or less Mn: 0.10-3.00%, P: 0.050% or less, S: 0.003% or less, Cr: 10.0-12.5%, Ni: 0.50-2.00%, N: 0.0200% or less, Cu: 2.00% or less, Al: 0.050% or less Including, C + N: 0.040% or less; The balance is Fe and unavoidable impurities, A welded joint made of martensitic stainless steel having a γmax of 75 or more as shown in formula 1, A martensitic stainless steel welded joint, characterized in that, when a histogram of crystal grain size is measured using EBSD (electron backscatter diffraction) in a coarse-grained region in a weld heat-affected zone of a cross section of the welded joint, the area ratio of crystals having a grain size of 0.04 mm or less is 80% or more. γmax=420C+470N+23Ni+9Cu+7Mn-11.5Cr-11.5Si-52×Al+189: Formula 1 In the formula 1, the element symbols indicate the content (mass%) of each element, and 0 is substituted when the element is not contained.
2. The martensitic stainless steel further comprises, in mass %, Mo: 1.00% or less, W: 0.50% or less, V: 0.300% or less, Sn: 0.100% or less, Ca: 0.0050% or less, Mg: 0.0050% or less, REM: 0.050% or less, Ti: 0.020% or less, Nb: 0.050% or less, B: 0.0050% or less, The welded joint of martensitic stainless steel according to claim 1, containing one or more of the following:
3. 3. The welded joint of martensitic stainless steel according to claim 1 or 2, which is a welded joint between the martensitic stainless steels.
4. A method for producing a welded joint of a martensitic stainless steel having the composition according to claim 1 or 2, comprising the steps of: A method for manufacturing a welded joint of martensitic stainless steel, characterized in that in a weld heat affected zone, the time during which the temperature remains at or above 1250°C is 8 seconds or less from the time when the temperature finally reaches or exceeds 1250°C due to heating by welding.
5. A welded structure having at least a portion thereof a welded joint made of the martensitic stainless steel according to claim 1 or 2.
Citation Information
Patent Citations
JP1974053521A
Martensitic stainless steel with excellent weld characteristics, and mertensitic stainless steel material
JP2011190521A
Method for producing circumferential weld joint for low-carbon martensite stainless steel tubing
WO2016088364A1